Confirmation of the Trends Suspected to be Present in the Tide of the Bay of Fundy - Godin, Gabriel (The International Hydrographic Review, 2015)
An additional set of data on the water level at Saint John, New Brunswick, covering the years 1932 to 1946, was exploited to reassess more closely the existence of rapid changes suspected to exist in the tide of the Bay of Fundy. The possibility of trends in the M2 tide had been suggested by DOODSON as early as in 1924 from a scrutiny of earlier data. Enough samples are now available to state unequivocally that the M2 tide is increasing at an accelerating rate and that S2 is diminishing. The characteristics of the trends are interpreted in terms of nonlinear frictional interactions.